1994
DOI: 10.1007/bf00666187
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor expression in breast cancer: Association with response to endocrine therapy

Abstract: 106 previously untreated breast cancer patients have been immunohistochemically analysed for EGF-R, ER, Ki67, and c-erbB-2 product. All patients received assessable endocrine therapy following disease progression. Significant associations were observed between EGF-R and ER (inverse) and Ki67 (direct). No association was observed between EGF-R and the c-erbB-2 product. EGF-R expression was significantly associated with the loss of endocrine sensitivity in breast cancer. This was observed in both ER positive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
99
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(107 citation statements)
references
References 14 publications
7
99
1
Order By: Relevance
“…This probably reflects the inverse relationship between EGFR and ERα expression that has been demonstrated in several studies on both cell lines and clinical material (Sainsbury et al 1985, Davidson et al 1987, Klijn et al 1994, Larsen et al 1999) and found to be associated with progression towards estrogen-independence and lack of response to endocrine therapy (Harris et al 1989, Nicholson et al 1994). In the estrogen-independent LCC cell system, however, the basal expression level of EGFR in MCF-7/LCC1 is dramatically increased compared with MCF-7 (DCS) but without a concomitant decrease in ERα mRNA level.…”
Section: Discussionmentioning
confidence: 79%
“…This probably reflects the inverse relationship between EGFR and ERα expression that has been demonstrated in several studies on both cell lines and clinical material (Sainsbury et al 1985, Davidson et al 1987, Klijn et al 1994, Larsen et al 1999) and found to be associated with progression towards estrogen-independence and lack of response to endocrine therapy (Harris et al 1989, Nicholson et al 1994). In the estrogen-independent LCC cell system, however, the basal expression level of EGFR in MCF-7/LCC1 is dramatically increased compared with MCF-7 (DCS) but without a concomitant decrease in ERα mRNA level.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, Watanabe and co-workers described a correlation between HER2 overexpression and the absence of estrogen receptors in breast carcinomas which is consistent with the non-responsiveness of HER2-positive tumours to endocrine therapy (Watanabe et al 1993, Nicholson et al 1994, Wright et al 1989.…”
Section: Egfr and Her2 Gene Aberrations In Human Cancersmentioning
confidence: 72%
“…The epidermal growth factor receptor (EGFR) 2 is considered a major oncogenic factor, and its presence in tumors is indicative of poor prognosis (1,2). EGFRs not only modulate growth properties of transformed cells but are causally involved in survival signaling, cell migration, angiogenesis, and metastasis (3)(4)(5).…”
mentioning
confidence: 99%